The Challenge of New Families - Ryrstedt, Eva (Columbia Journal of Gender and Law, 2010)
Today there are many new and different types of families-not only families with one biological parent and one step-parent, but also families with same-sex parents or with two sets of same-sex parents who together with the child form a household. These new families pose many new challenges for society. One such challenge is how to allocate different social benefits that were traditionally designed for the nuclear family or for a single parent with sole legal custody of a child. Families with a single parent and a non-custodial or joint custodial parent who spends some time with the child and families with one biological parent and one stepparent already pose certain problems. Such families mean there may be other parental figures out there claiming that the child is part of their family. As even more complex families emerge, the potential for problems is readily apparent.